2017
DOI: 10.1007/s10616-017-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study and evaluation of cytotoxicity, mutagenicity, cell cycle kinetics and gene expression of Bauhinia holophylla (Bong.) Steud. in HepG2 cells in vitro

Abstract: Bauhinia holophylla (Bong.) Steud. (Fabaceae) is a plant used in Brazilian folk medicine to treat diabetes and inflammation. This study evaluated the phytochemical properties, cytotoxic, apoptotic, mutagenic/antimutagenic effects and alterations in gene expression (RNAm) in HepG2 cells treated with the B. holophylla extract. The phytochemical profile highlight the presence of flavonoids isorhamentin and quercetin derivates. The MTT assay was used to evaluate the cytotoxicity of different concentrations for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The anti-inflammatory activities were evaluated as the decrease in the production of the pro-inflammatory cytokines TNF-α and interleukin-6 (IL-6) and the increase of the level of the anti-inflammatory cytokine IL-1 [ 97 ]. Anti-ulcer activity has also been described in models of acute gastric lesion induced in rats or mice, and aqueous extracts promoted an increase in the amount of gastric mucus [ 99 ]. The potential gastroprotective activity is possibly mediated by flavonols.…”
Section: Biological Activitymentioning
confidence: 99%
“…The anti-inflammatory activities were evaluated as the decrease in the production of the pro-inflammatory cytokines TNF-α and interleukin-6 (IL-6) and the increase of the level of the anti-inflammatory cytokine IL-1 [ 97 ]. Anti-ulcer activity has also been described in models of acute gastric lesion induced in rats or mice, and aqueous extracts promoted an increase in the amount of gastric mucus [ 99 ]. The potential gastroprotective activity is possibly mediated by flavonols.…”
Section: Biological Activitymentioning
confidence: 99%
“…Flavonoids from B. holophylla showed a significant antiviral effect against the Dengue virus, which also belongs to the Flaviviridae family [14]. Ribeiro et al [15] and Marena et al [16] reported the absence of cytotoxic and mutagenic effects, as well as antimicrobial effects of hydroalcoholic leaf extract, suggesting that B. holophylla has potential as an herbal medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral effects were also described by Santos et al [ 28 ] against the dengue virus. Recently, Ribeiro et al [ 29 ] and Marena et al [ 30 ] reported the absence of cytotoxic and mutagenic effects, and even protective activity against known carcinogens, as well as antimicrobial effects of hydroalcoholic leaf extract, suggesting that B. holophylla has potential as a herbal medicine.…”
Section: Introductionmentioning
confidence: 99%